Treatment registry for outcomes in patients with castration-resistant prostate cancer (TRUMPET): a methodology for real-world evidence and research. (December 2016) - Penson, David F; Lin, Daniel W; Karsh, Lawrence; Quinn, David I; Shevrin, Daniel H; Shore, Neal; Symanowski, James T; Brown, Bruce; Forer, David; Wong, Elaine K; Flanders, Scott C
Aim: This study seeks to improve the understanding of treatment patterns and associated health-related quality of life (HRQoL), clinical outcomes and healthcare utilization in US patients with castration-resistant prostate cancer (CRPC).Patients & methods: Treatment Registry for Outcomes in CRPC Patients (TRUMPET) is a US-based, prospective, observational multicenter registry (NCT02380274) involving patients with CRPC and their caregivers. Patients initiating their first active treatment course will be enrolled from urology and medical oncology practices, with data captured up to 4 years.Results: Information on prescribing patterns, HRQoL, clinical outcomes and healthcare utilization will be collected.Conclusion: TRUMPET will enable scientific understanding of disease management in terms of HRQoL, clinical outcomes and healthcare utilization in clinical practice for patients with CRPC.